2020
DOI: 10.2106/jbjs.20.00660
|View full text |Cite
|
Sign up to set email alerts
|

Improving Management of Adult Ankle Fractures in Malawi

Abstract: Background: The burden of musculoskeletal trauma is increasing worldwide, especially in low-income countries such as Malawi. Ankle fractures are common in Malawi and may receive suboptimal treatment due to inadequate surgical capacity and limited provider knowledge of evidence-based treatment guidelines. Methods: This study was conducted in 3 phases. First, we assessed Malawian orthopaedic providers’ understanding of anatomy, injury identification, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This suggests that OCOs were less likely than surgeons to recommend surgery for the same injuries, underscoring the importance to train OCOs in evidence-based and standardized guidelines delineating which fractures should be treated conservatively and which should be referred for surgery. 49 To ensure surgical capacity for evidence-based referrals, the training and recruitment of more orthopaedic surgeons must be prioritized.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that OCOs were less likely than surgeons to recommend surgery for the same injuries, underscoring the importance to train OCOs in evidence-based and standardized guidelines delineating which fractures should be treated conservatively and which should be referred for surgery. 49 To ensure surgical capacity for evidence-based referrals, the training and recruitment of more orthopaedic surgeons must be prioritized.…”
Section: Discussionmentioning
confidence: 99%
“…Given most of the participants’ limited resources and lack of soft-tissue specialists, particularly for Interior Committee groups, a phase 3 study to create a specific didactic and hands-on wound coverage technique course could improve open tibia fracture management and treatment standardization. [ 28 ] Previous studies in LMICs have reported on the efficacy of such courses, including improving patient outcomes and reducing long-term disability. These courses educate orthopedic surgeons on the basic principles and techniques of open fracture management and lower extremity flap reconstruction procedures, with an emphasis on challenges faced in resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, of 17 wound care and operating room resources, Negative Pressure Wound Therapy was the only resource that was reported available to more than half of the participants. Given most of the participants’ limited resources and lack of soft-tissue specialists, particularly for Interior Committee groups, a phase 3 study to create a specific didactic and hands-on wound coverage technique course could improve open tibia fracture management and treatment standardization [28] . Previous studies in LMICs have reported on the efficacy of such courses, including improving patient outcomes and reducing long-term disability.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to improve pediatric orthopaedic surgical capacity in Malawi and other similar settings. This will likely require standardization of treatment practices, advanced training of local providers, improved resource procurement, and investment in health-system infrastructure 15,16,[54][55][56][57] . In Malawi, operative orthopaedic surgical capacity is present only in central hospitals.…”
Section: Discussionmentioning
confidence: 99%